Synthesis and reactivity of electron-deficient phosphorus(III) compounds - Dordevic, Nemanja (2017)
Our work reflects efforts to increase the Lewis acidity of two-coordinate phosphorus(III)-based compounds for the purpose of small molecule activation. In this view, we tuned the electronic properties of phosphenium ions by increasing their overall positive charge and by varying the extent of π-donation from the neighboring substituents to the central P atom. Synthetic methodology for generation of di- and tricationic phosphenium salts is based on exceptional electron-donating properties of carbone ligands. Initial attempts to generate isolable phenyl- ([(Ph3P)2C.PR]2+, R = Ph, [1a]2+), 4-fluorophenyl- (R = 4-F-Ph, [1b]2+), methoxy- (R = OMe, [1e]2+), and tert-butyl-substituted (R = tBu, [1d]2+) phosphenium dications stabilized by carbodiphosphorane (Ph3P)2C, 1 are described. Transient formation of [1a]2+ and [1b]2+ is evidenced by activating C-F bonds of trifluorotoluene and [BArF4]- (ArF = (CF3)2-C6H3) anion. The replacement of carbodiphosphorane 1 with more nucleophilic and sterically less demanding carbodicarbene ligand {C6H4(MeN)2C}2C, 2 resulted in a series of P-dications [{C6H4(MeN)2C}2C.PR]2+ (R = NiPr2, Ph, OMe, tBu, Cl) whose spectroscopic and structural features are presented. Uniting electron donor capabilities of two carbodicarbene molecules afforded the first example of two-coordinate phosphenium trication [({C6H4(MeN)2C}2C)2P]3+, [(2)2P]3+ whose interesting bonding features are studied using modern computational methods. In addition to the increased overall positive charge, cooperative enhancement of Lewis acidity by bringing two dicationic P centers in close proximity is also attempted. However, these attempts yielded reaction products derived from an unexpected P-N bond cleavage whose mechanistic details are disclosed. The last portion of this work is focused on the activation of enthalpically strong E-H bonds (E = B, Si, C) using carbodicarbene-stabilized P-dications. Reaction products formally derived from E-H insertion and/or hydride abstraction are isolated and fully characterized. The preference of [{C6H4(MeN)2C}2C.PPh]2+, [2a]2+ and [{C6H4(MeN)2C}2C.PNiPr2]2+, [2c]2+ to cleave rather than to insert into Si-H bond, as well as the surprising formation of carbodicarbene-supported parent phosphenium ion [{C6H4(MeN)2C}2C.PH2]+, [2.PH2]+ are experimentally verified.